(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Metabolic syndrome is one of the most common chronic diseases in the world today. Its spread is so great that it has become a non-contagious epidemic. Obesity creates the basis for the development of a number of cardiovascular diseases. Metabolic syndrome remains one of the main etiological factors, especially in the development of atrial fibrillation. Lipotoxic damage to the heart is one of the important mechanisms for the development of various forms of ventricular fibrillation.